Geographic variability in taxonomic composition, standing stock, and productivity of the mesozooplankton community around the Kuroshio Current in the East China Sea. (7th May 2018) - Kobari, Toru; Makihara, Wataru; Kawafuchi, Takahiro; Sato, Kie; Kume, Gen
Abstract: Despite the low productivity that has been thought to characterize plankton communities in the western boundary current of the North Pacific Subtropical Gyre, many migratory fishes risk encountering low food availability during crucial life history stages by reproducing and recruiting in the Kuroshio region (i.e., the Kuroshio Paradox). Here, we report on geographic variability in taxonomic composition, biomass, and productivity of the mesozooplankton community in the Kuroshio Current and neighboring waters in the East China Sea. Calanoid copepods were the most abundant mesozooplankton taxon throughout our sampling stations. Small copepods, which include nauplii and poecilostomatoids, and gelatinous metazoans were the next most abundant. Seasonal variability in mesozooplankton standing stock (i.e., abundance and biomass) and productivity (i.e., production rate and protein synthetase activity) exceeded spatial variability across the stations and regions. The mesozooplankton community was characterized by high biomass and production rates in the summer, as well as high abundance and protein synthetase activity in the fall. No significant differences were found for mesozooplankton standing stock and productivity in the Kuroshio Path relative to those on the continental shelf or on the outside of the Kuroshio Path. Our results indicate that the standing stock and productivity of the mesozooplankton community in the Kuroshio Path are equivalent to those on the continental shelf, and that these communities are supported by small copepods and gelatinous zooplankton. We suggest that the mesozooplankton standing stocks and productivity provide adequate food availability for migratory fishes in the Kuroshio and neighboring waters in the East China Sea.